2015
DOI: 10.1007/s13592-015-0414-6
|View full text |Cite
|
Sign up to set email alerts
|

Stock composition of northern neotropical honey bees: mitotype and morphotype diversity in Mexico (Hymenoptera: Apidae)

Abstract: -The stock of honey bees in the northern neotropics is likely a composite of European and African lineages, but the genetic makeup of most populations in this region has remained unstudied. We analyzed the genetic composition of honey bees across temperate and tropical regions of Mexico using mitochondrial and morphometric analyses. The results showed that honey bees from Mexico are descendent almost in similar proportion from matrilines of African and European origins. However, morphometrics indicate that mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
0
10
0
3
Order By: Relevance
“…The effects of N. ceranae on honey bees from tropical regions have been poorly documented, mostly limited to reports of the presence of this microsporidium in different countries (Guzmán-Novoa et al 2011;Teixeira et al 2013;Santos et al 2014). In tropical and subtropical Mexico, Africanized honeybee (AHB) colonies are predominant (Domínguez-Ayala et al 2016). In Brazil, laboratory studies have confirmed a reduced survival of Africanized honey bee workers infected with N. ceranae under controlled conditions (Gregorc et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of N. ceranae on honey bees from tropical regions have been poorly documented, mostly limited to reports of the presence of this microsporidium in different countries (Guzmán-Novoa et al 2011;Teixeira et al 2013;Santos et al 2014). In tropical and subtropical Mexico, Africanized honeybee (AHB) colonies are predominant (Domínguez-Ayala et al 2016). In Brazil, laboratory studies have confirmed a reduced survival of Africanized honey bee workers infected with N. ceranae under controlled conditions (Gregorc et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the process of Africanization of Mexico's honey bees seems to have stabilized to a large extent (Domínguez-Ayala et al, 2016). In general, the honey bees of Mexico show evidence that hybridization has occurred extensively and that climate drives introgression of African genes into local populations.…”
Section: History and Genetic Makeup Of Ahbs In Mexicomentioning
confidence: 97%
“…Recently, a comprehensive study including 500 colonies collected from the five beekeeping regions of Mexico yielded a better picture of the current genotypic composition of honey bees in the country (Domínguez-Ayala et al, 2016). About half of the colonies sampled (51.5%) had African mitotypes.…”
Section: History and Genetic Makeup Of Ahbs In Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…The tropical Yucatan Peninsula of Mexico is among the top beekeeping areas in the world (Echazarreta et al 1997). Indeed, the most productive beekeeping is practiced in the tropical and subtropical areas of Mexico where AHBs are predominant (Quezada-Euán 2007; Domínguez- Ayala et al 2016). Environmental temperatures in the Peninsula can reach up to 45°C during the dry season between April and June (Poot-Báez 2018).…”
Section: Introductionmentioning
confidence: 99%